Between Tradition and Sharia: Endogamous Marriage Practices in the Pesantren Community of Bandung Regency from a Contemporary Islamic Legal Perspective - Harry Yuniardi; Diah Siti Sa’diah; Aziz Sholeh; Lena Ishelmiany Ziaharah; Christopher Michael Cason (Faculty of Sharia, IAIN Metro, 2025)
This study aimed to examine the practice of endogamy in the Pesantren community of Bandung Regency from the perspective of contemporary Islamic law, by highlighting the tension between social traditions and more universal sharia principles. Endogamy, as a practice of marriage between Pesantren residents, is believed to preserve Islamic values, maintain the honour of the nasab, and strengthen internal social networks. This research used a descriptive qualitative approach through field research, supported by quantitative survey data and normative analysis based on the theory of maqāṣid al-syarī'ah, legal sociology, and contemporary reinterpretation of tradition (urf). Data were obtained through questionnaires and in-depth interviews with students, alumni, and Pesantren leaders. The study results showed that most Pesantren residents supported the practice of endogamy for the similarity in values and maintaining the compatibility of couples based on the principle of kafā'ah. However, most respondents also realized this practice was more traditional than religious. On the other hand, the younger generation had a strong tendency to reassess the relevance of endogamy and the concept of kafā'ah in the modern context. This study concludes that the practice of endogamy and the meaning of kafā'ah in the Pesantren community need to be re-reflected through a contemporary Islamic legal approach that emphasizes the principles of justice, benefit, and respect for individual rights. These findings are expected to encourage a transformation of thinking in the Pesantren community towards a more contextual, inclusive, and progressive understanding of Islamic law.